2012
DOI: 10.1007/s10654-012-9698-2
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic radiation and mortality from cancer among male German airline pilots: extended cohort follow-up

Abstract: Commercial airline pilots are exposed to cosmic radiation and other specific occupational factors, potentially leading to increased cancer mortality. This was analysed in a cohort of 6,000 German cockpit crew members. A mortality follow-up for the years 1960-2004 was performed and occupational and dosimetry data were collected for this period. 405 deaths, including 127 cancer deaths, occurred in the cohort. The mortality from all causes and all cancers was significantly lower than in the German population. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
6
15
0
Order By: Relevance
“…Several studies have found a non‐significant increase in prostate cancer mortality or incidence [Band et al, ; Irvine and Davies, ; Rafnsson et al, ; Pukkala et al, ]. In agreement with other studies [Blettner et al, ; Zeeb et al, ], we did not observe an excess in mortality from prostate cancer, a hormone‐related cancer which may be associated with circadian rhythm disruption [Hammer et al, ]. However, cumulative time zones crossed but not work at night as a metric of circadian rhythm disruption was shown to be strongly correlated with the estimated cumulative cosmic radiation dose in the Pan Am flight attendant study [Pinkerton et al, ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several studies have found a non‐significant increase in prostate cancer mortality or incidence [Band et al, ; Irvine and Davies, ; Rafnsson et al, ; Pukkala et al, ]. In agreement with other studies [Blettner et al, ; Zeeb et al, ], we did not observe an excess in mortality from prostate cancer, a hormone‐related cancer which may be associated with circadian rhythm disruption [Hammer et al, ]. However, cumulative time zones crossed but not work at night as a metric of circadian rhythm disruption was shown to be strongly correlated with the estimated cumulative cosmic radiation dose in the Pan Am flight attendant study [Pinkerton et al, ].…”
Section: Discussionsupporting
confidence: 91%
“…A non‐significant elevation in CNS (including brain) cancer mortality was reported in the British Airways study [Irvine and Davies, ] and the pooled European study [Blettner et al, ]. CNS (including brain) cancer mortality was significantly elevated in the German cockpit crew with a significant trend for the duration of employment [Zeeb et al, ] and a non‐significant trend for radiation dose [Hammer et al, ]. In this cohort, a non‐significant elevation of CNS (including brain) cancer mortality based on 32 cases was observed.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…They compared mortality to the general population of Germany and conducted dose-response assessment within the cohort for certain cancers. As noted for previous follow-up of the same cohort,1 3 4 large deficits in mortality for most causes were observed compared with the general population, in particular deficits of 16% to 73% for all-cause, all-cancer and lung cancer mortality, which suggests a continued strong healthy worker effect. Dreger and colleagues2 observed an excess of mortality from cancers of brain and colon and of melanoma of skin compared with the general population; however, positive associations were not seen between cosmic radiation and any studied outcome.…”
supporting
confidence: 73%
“…The cohort of 6000 pilots was studied between 1960 and 2004 (Hammer et al, 2012). Per this study 127 members of flight personnel died of cancer among total of 405 deaths.…”
Section: Civil Flight Statistics and Studies Regarding Radiation Impamentioning
confidence: 99%